A noção de equivalência e a sua especificidades na tradução juramentada - Chanut, Maria Emília Pereira [UNESP] (My University, 2012)
We propose in our study a reflection on “functional equivalence” based on a comparative/ terminological bilingual (Portuguese from Brazil/ French from France) approach of specialized texts (certified) due to difficulties that are aggravated by particularities from Switzerland French. A presentation of the equivalence notion in translation theories is necessary to introduce the central issue of this article, namely, to show that “the functional equivalence” seems, in the case of the specialized translation, most appropriate. This happen because legal terms and/or legal gifts in official documents are, in its essence, culturally marked, presenting a direction or different use, even though improper in countries that speak the same language, such as France and Switzerland.

Este estudo, partindo de uma abordagem comparativa/terminológica bilíngue (português do Brasil/francês da França) de textos especializados (juramentados), cujas dificuldades são agravadas por particularidades do francês da Suíça, propõe uma reflexão sobre a “equivalência funcional”. Uma apresentação das teorias referentes à noção de equivalência em tradução nos serve para introduzir a ideia central deste artigo, a saber, mostrar que a equivalência “funcional” é, no caso da tradução especializada, a mais apropriada, uma vez que os termos legais e/ou jurídicos presentes nos documentos oficiais são, em sua essência, culturalmente marcados, podendo apresentar sentido ou uso diferente e até mesmo equivocado em países que falam a mesma língua, tais como a França e a Suíça.
Keywords: equivalência funcional; tradução especializada; conteúdo cultural; francês da França; francês da Suíça; português do Brasil; functional equivalence; specialized translation; cultural content; French from France; Switzerland French; Portuguese from Brazil